New Solutions for the Heart An Update in Advanced Perioperative Protection - Podesser, Bruno K.; Chambers, David J.; SpringerLink (Online service) (Vienna : Springer Vienna : Imprint: Springer, 2011)
Although cardiac surgery has made an enormous progress during the last decades, the discipline has to cope with essential changes: Patients are increasingly cared for by cardiologists and therefore referred to the surgeon in a later stage of disease. Consequently, they are more often in an increasingly serious state or in advanced age with significant comorbidities. In order to meet the requirements of these different patient groups, cardiosurgical treatments require special protectional strategies for the heart in order to perform the planned operations safely. This book presents the latest knowledge of modern techniques of myocardial protection taking into consideration the different patient groups and current scientific strategies. Furthermore, it discusses present and future scientific approaches in myocardial protection and preservation.
Preface -- 1. Why do we need new approaches in myocardial protection?- 1.1.The geriatrician$1 (Bs and epidemiologists view -- 1.2.The surgeon$1 (Bs view -- 2. Fundamental developments of the past -- 3.Sites of injury -- 3.1.The endothelium -- 3.2.The myocyte -- 3.3.The conductance system -- 4. Special needs in clinical myocardial protection -- 4.1.Protection in the neonatal -- 4.2.Protection in the hypertrophied/failing heart -- 4.3.Protection of the senescent heart -- 4.4.Protection of the right heart -- 4.5.Protection during heart transplantation -- 5. Possible new approaches and concepts -- 5.1.The endothelium as a target -- 5.2.Vascular facts including angiogenesis of cardioplegia -- 5.3.Continuous perfusion during procurement/transport -- 5.4.Optimizing metabolims/anaplerosis -- 5.5.Alternative solutions for the heart -- 5.6.Radical scavangers in cardioplegia -- 5.7.Visualization techniques in cardioplegia -- 5.8.The coronary sinus: an alternative route for cell-TX.s
Keywords: Medicine; Anesthesiology; Cardiology; Heart -- Surgery; Transplantation of organs, tissues, etc; Medicine & Public Health; Cardiac Surgery; Transplant Surgery; Cardiology; Anesthesiology